Self-determination theory in teaching practice for higher education level - Sahril Nur; Muh Safar Nur; Rahayu Rahayu; Mardiani Mardiani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
This study aims to gain a deeper understanding of how self-determination theory is implemented in higher education. This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. The systematic review begins with an analysis of the identification procedure. Next, the best papers published between 2012 and 2022 were selected to explain how to compare significant aspects and efficient methods. The significance of self-determination theory to the evolution of the teaching profession determined the selection of these papers. The results are divided into three categories, with the following themes emphasizing the examined literature the most. Researchers use their findings to maximize the implementation of SDT in the classroom. The second section consists of data collection. Questionnaires, interviews, pre-and post-tests, and online discussion forums were used for data collection. Finally, the researcher has created a list of several published issues for analysis based on the most recent study themes.DOI: 10.26905/enjourme.v7i1.7978